Ensino religioso: a pedagogia do como e do quê ensinar - Santos, José Carlos do Nascimento (2017)
This dissertation entitled Religious Education: pedagogy of how and what to teach. It aimed to investigate the about how the Religious Education in the classroom is being developed. Regarding this, article 33 of the LDB affirms that the optional enrollment RE is an integral part of the basic education of the citizen and constitutes discipline of the normal hours of public elementary schools, ensuring respect for the cultural diversity of Brazil, Forms of proselytism. (Redaction given by Law No. 9,475, dated 22.7.1997) through the cited article, the RE is a discipline that requires special attention in pedagogical praxis, since it is a discipline inserted in school curricula and in the Basic training of the citizen (â). Our research had a bibliographic, descriptive and field typology. The same had been done in the EEEFM "ODILON NELSON DANTAS" located in the city of Cuitegi-PB. In order to collect the data, we developed and applied a semistructured questionnaire with 03 teachers, of which 01 were in each shift of Elementary School II in the school mentioned above. We suggest as methodological support and contribution to ER teaching techniques for the 6th to 9th grade classes according to the content organized by the PCNER. With the purpose of fulfilling the proposed objective, the research is organized in 03 chapters. In the first, we present the historical aspect of RE at national, state and municipal level, its trajectories, obstacles, resistances and conceptions. In the second chapter, we emphasize the didactic-pedagogical part, its methodology, teacher training, FONAPER's importance in ER epistemology, as well as the program content contained in the PCNER. In the third and last chapter, we deal with the analysis of the research and its contributions to the practice of RE. In order to justify this article, we cite in our referential several theorists that work with the theme in Pedagogy of the RE. We identify with the results of the research that much must be done in favor of this important discipline in the curriculum. The lack of commitment to this discipline is evident from the withdrawal of the same from the 3rd version of BNCC. Another aggravating factor is the lack of pedagogical accompaniment and didactic material for teachers. Finally, teachers do not have the specific training to act in the classroom.